ANALISIS KESIAPAN CREW DALAM LAUNCHING DAN RECOVERY SEKOCI DI KMP. LABITRA KARINA - Rara Zufriani; Achmad Ali Mashartanto; Bayu Yudho Baskoro; Naf'an Arifian; Langandriansyah Dwi Yatno (STKIP Subang, 2026)
This study aims to analyze the readiness of the ship's crew in launching and recov- ering lifeboats and the factors that influence it on KMP Labitra Karina. The readiness of the crew in operating lifeboats is very important in dealing with emergencies at sea, especially when evacuating passengers and crew. The research method used was a qualitative descriptive method with data collection techniques through observation, interviews, and documentation. The results showed that the crew's readiness in launching and recovering lifeboats on the KMP Labitra Karina was established but not yet optimal.